Visual Culture as a Strategy for Teaching Contemporary Geometry: Reflections and Proposals - Méndez-Reyes, Johan; González-Rivera, Pedro; Cadena-Figueroa, Marcela Elizabeth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article proposes a pedagogical reflection on the importance of raising teachers' awareness to recognize the value of the urban environment, especially the architecture of Guayaquil, as a visual resource for teaching geometry. From a qualitative and descriptive approach, a theoretical review is conducted, and using visual culture as a connecting axis, three buildings with geometric richness and heritage value are presented, along with a didactic sequence. Additionally, an educational itinerary with technological extension is proposed that projects the proposal into the 21st century. It invites us to re-signify the city as an expanded classroom and visual text.